ANALISIS FITOKIMIA, AKTIVITAS ANTIOKSIDAN DAN ANTIBAKTERI DAUN ANDONG (Cordyline fruticosa) - Andani, Lowisesi; Sari, Nur Maulida; Salusu, Heriad Daud; Yusdiansyah; Wartomo; Prayitno, Joko; Aryani, Farida (PERENNIAL, 2022)
The Andong Merah plant (Cordyline fruticosa) is known to have natural antibacterial properties, which can inhibit the growth of cancer and tumors. Several studies that have been carried out previously showed the potential of red Andong Merah plant extracts for health, especially in the Andong Merah leaves with many active compounds. This study explored the potential of Andong Merah leaves for their phytochemical analysis, antioxidant and antibacterial activity. Andong Merah leaves were macerated using n-hexane, ethyl acetate, and ethanol solvent to yield the crude extracts. The phytochemical analysis was evaluated by the Harborne and Kokate method. Antioxidant activity was evaluated by DPPH radical scavenging assay. Antibacterial activity was examined using the agar well diffusion method against Propionibacterium acnes, Streptococcus mutans, and Streptococcus sobrinus. The results showed that the Andong Merah leaves extract contains alkaloids, flavonoids, tannins, steroids, and saponins. The antioxidant activity test showed that the n-hexane and ethyl acetate of Andong Merah leaves extracts displayed the ability to inhibit DPPH free radical by 74% and 75% at 200 ppm concentration, while ethanol extracts by 79% at 100 ppm concentration. The antibacterial activity showed that the ethanol extract of Andong Merah leaves displayed the ability to inhibit the Propionibacterium acnes growth with 12 mm inhibition activity at 400 µg. The ethanol and ethyl acetate of Andong Merah leaves extract can inhibit the Streptococcus mutans growth with 9 mm at 400 µg. Antibacterial activity of n-hexane, ethyl acetate, and ethanol extract of Andong Merah leaves display the ability to inhibit the Streptococcus sobrinus growth with 10 mm at 400 µg concentration. Based on the results, Andong Merah leaves (Cordyline fruticosa) display potential as a natural antioxidant and antibacterial agent.